2017
DOI: 10.1371/journal.pone.0169371
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Regimes, Starvation and Age on Heat Tolerance of the Parthenium Beetle Zygogramma bicolorata (Coleoptera: Chrysomelidae) following Dynamic and Static Protocols

Abstract: Temperature and resource availability are key elements known to limit the occurrence and survival of arthropods in the wild. In the current era of climate change, critical thermal limits and the factors affecting these may be of particular importance. We therefore investigated the critical thermal maxima (CTmax) of adult Zygogramma bicolorata beetles, a biological control agent for the invasive plant Parthenium hysterophorus, in relation to thermal acclimation, hardening, age, and food availability using stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 81 publications
4
83
0
Order By: Relevance
“…Hence such plasticity, or lack thereof, may mediate the host–parasitoid interactions in tropical agroecosystems in current and future climate change scenarios. Several studies investigating different insect taxa have also reported such RHH and demonstrated its potential to improve survival in rapidly changing thermal environments . Similarly, RHH also improved survival of C. partellus pupae and adults (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Hence such plasticity, or lack thereof, may mediate the host–parasitoid interactions in tropical agroecosystems in current and future climate change scenarios. Several studies investigating different insect taxa have also reported such RHH and demonstrated its potential to improve survival in rapidly changing thermal environments . Similarly, RHH also improved survival of C. partellus pupae and adults (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Kalra et al ., ), such correlations between traits of starvation and heat tolerance have been generally limited and showed no significant cross‐tolerance (see Bubliy et al ., ). A nonsignificant relationship between starvation and thermal tolerance has been observed in Ceratitis species (Nyamukondiwa & Terblanche, ), Drosophila melanogaster (Bubliy et al ., ), Tribolium castaneum (Scharf et al ., ) and Zygogramma bicolorata (Chidawanyika et al ., ). However, the current study suggests otherwise and points to possible mechanistic associations between starvation and heat tolerance (also see Kalra et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…longevity, fungal resistance and climbing activity [30]. Therefore, we also examined gene expression of decorin, one of proteoglycan type myokines produced and released by skeletal muscle cells ( Figure 3D).…”
Section: Effect Of Starvation On Expression Of Troponin Complex Genesmentioning
confidence: 99%